Hydrodynamic modelling in marginal and coastal seas — The case of the Adriatic Sea as a permanent laboratory for numerical approach. (November 2022) - Umgiesser, Georg; Ferrarin, Christian; Bajo, Marco; Bellafiore, Debora; Cucco, Andrea; De Pascalis, Francesca; Ghezzo, Michol; McKiver, William; Arpaia, Luca
Abstract: Understanding the water circulation in oceans and coastal seas is among the key topics of oceanographic and climate research. Hydrodynamic studies form the basis for many oceanographic subjects, whether sediment transport, morphology, water quality, ecological and climate changes are being investigated. Hydrodynamic modelling of oceans and coastal seas has become a fundamental tool for describing the dynamics of marine environments, revealing the human impact on the sea and promoting sustainable development of marine resources. By complementing – through data assimilation – more and more diffuse and integrated global and regional observing systems (composed of coastal gauges, moorings, buoys, satellites, drifters), hydrodynamic models provide a deterministic 4D view of the ocean state. In this context, the semi-enclosed Adriatic Sea represents a natural long-standing laboratory for hydrodynamic modelling. The peculiar historical, morphological and oceanographic characteristics of this basin and its complex coastline stimulated over decades the development and application of several ocean and coastal models. In this work, we review different aspects of hydrodynamic modelling covered by the literature, highlighting the wide variety of model applications carried out in the Adriatic Sea which could serve as examples for semi-enclosed, marginal and coastal seas worldwide. Within the scope of the review, we find that although significant progress has been made over the last few decades, most of the modelling studies underrate the importance of a detailed representation of the land-coastal-sea fluxes. We list a set of recommendations that can be used as guidelines for model implementation to broaden the applicability of hydrodynamic models in future studies. Finally, we discuss the remaining questions that still need to be further explored. Highlights: An overview of the present state of the art in coastal and marginal seas hydrodynamic modelling. The semi-enclosed Adriatic Sea represents a natural long-standing laboratory for model development. A set of examples that can be used as guidelines for different model applications. A look and a prospect for the corresponding possible future developments.